Study Eksperimental Karakteristik Penyalaan Minyak Kelapa Sebagai Bahan Bakar Alternatif Dengan Penambahan Bioaditif Minyak Kayu Putih - Timang, Rison Sando; Riupassa, Helen; Nanlohy, Hendry Y. (Rekayasa Material, Manufaktur dan Energi, 2024)
The limited availability of diesel oil encourages efforts to find new energy sources as alternative diesel fuels. Biodiesel can be extracted from various agricultural products, for example, coconut oil. As a tropical country, Indonesia is a very effective and potential country as a coconut producer. Vegetable oil has a higher viscosity than diesel oil. Compose bio-oils with various fuels additive is the way to reduce viscosity values, among others, by combining nanocarbon and metal catalysts. This study goals to know the characteristics of burning coconut oil as an alternative fuel with the addition of eucalyptus oil; and how long the combustion process takes from the starting point to the end. The results showed that adding eucalyptus oil to coconut oil can reduce the weakening of the carbon chain and increase the combustion temperature. The combustion efficiency of this coconut oil mixture varies depending on the amount of eucalyptus oil added, resulting in faster fuel combustion and a more powerful explosion. The color of the fire is an essential factor in ensuring that this mixture can be used safely and efficiently.